Resurrection and typification of Elatine campylosperma (Elatinaceae), a long-forgotten waterwort species - Attila Takács; Attila Molnár V.; Balázs A. Lukács; Timea Nagy; Ádám Lovas-Kiss; Andy J. Green; Agnieszka Popiela; Lajos Somlyay (PeerJ, 2018)
The name Elatine campylosperma Seub. is generally treated as one of the synonyms of E. macropoda Guss. However, recent morphological, phylogenetic and karyological studies indicate that this judgement should be revised. In the present paper we typify the name E. campylosperma, review its taxonomic history and provide a thorough description, with compilation of previously published data and our new measurements from in vitro cultures. Based on our herbarium survey, we outline its Atlantic-Mediterranean distribution area (Spain, France, Italy, Greece, Turkey and Algeria). Habitat preferences are summarized from our field observations, water quality measurements and the label information of the herbarium specimens examined. Intact E. campylosperma seeds were found in faecal samples of the Eurasian Coot (Fulica atra L.) in southern Spain and two of them were germinated, suggesting that E. campylosperma has a capacity for long distance dispersal via endozoochory.